A Facile Route to Prepare PMMA/SiO2 Core‐Shell Particles and PMMA Microcapsules via Sonochemical Graft Polymerization. Issue 14 (10th April 2019) - Guo, Sheng‐Wei; Wang, Xin; Wang, Gu‐Xia; Nie, Min
Abstract: Ultrasonically initiated graft polymerization is employed to prepare poly (methyl methacrylate)/silicon dioxide (PMMA/SiO2 ) core‐shell particles and PMMA microcapsules. Monodisperse SiO2 particles are obtained by the Stöber method. Its surface is modified with γ‐methacryloxypropyl trimethoxy silane (MPS) to introduce unsaturated double bonds. And then MMA and MPS are copolymerized under ultrasonic initiation to prepare PMMA/SiO2 core‐shell particles. PMMA microcapsules are obtained by etching SiO2 with the HF aqueous solution. The morphology and size of the core‐shell particles and polymer microcapsules are analysed using transmission electron microscopy (TEM) and dynamic light scattering (DLS). The encapsulation state is determined using a Fourier transform infrared spectrometer (FTIR) and X‐ray photoelectron spectrometer (XPS). The results show that both the core‐shell particles and the polymer microcapsules have perfect core‐shell or hollow structures. The control of shell thickness can be easily realized by adjusting the amount of monomer, e. g. 30 nm, 50 nm and 80 nm, respectively. And in the inner of the shell, PMMA is anchored onto the surface of SiO2 core with covalent bonds. As the monomer amount increases, the contents of Si, O, and C change accordingly. And the polymer shell would become denser and thicker. Abstract : Organic‐inorganic (PMMA/SiO2 ) core‐shell microspheres were simply fabricated through ultrasonically initiated graft polymerization. And the polymer microcapsules could be obtained after etching the inorganic cores with the HF aqueous solution. Both the size and the shell thickness of the mcirospheres/microcapsules were easily controlled. The study proved that sonochemistry is a simple, clean and efficient technique for preparing this type of functional polymer materials.